ERGONOMI PARTISIPATIF DALAM PEMBUATAN BUKU DIGITAL GUYUP KOPERASI PENGELOLA SAMPAH - Helena Juliana Kristina; Lithrone Laricha Salomon (PROSIDING SERINA, 2021)
Based on the results of the webinar "Pengenalan Pra Koperasi dan Koperasi Bank Sampah", on June 9th 2021, the PKM team and Pepulih partners felt the need to continue educational activities regarding the introduction of pre-cooperatives or cooperatives for waste management. It is also realized that the Covid-19 pandemic has affected the economy and the life of the Indonesian people, which also has an impact on the waste bank community and waste management. For this condition, the best way for the community's economic recovery is to establish and join a  placed  called Koperasi (cooperation). But the problem is that the waste management cooperation is not widely known to the public, and the forms and activities in the waste management cooperation that are suitable for the community are still being questioned. The solution that the PKM team offered to Pepulih partners is to continue the collaboration was to make a digital book with the theme: Buku digital Guyub Koperasi Pengelola Sampah. This digital book was created as a sign of appreciation for community members who have been and are currently pioneering efforts to establish a Waste Management Cooperation in their area. The method that has been used is participation, because based on previous PKM activities, it is known that activities promoting environmental conservation behavior can be carried out through self-actualization activities based on a participatory ergonomics approach, which invites the public, company agencies, communities and government to participate in writing manuscripts which are then published through digital books. The author's participants are practitioners of waste management cooperatives, teachers, observers, and related governments. The purpose of this book is to serve as a means of educating the public, that only through the Waste Management Cooperation, we can strive for Mutual Welfare. The output of this PKM is a digital book with an E-ISBN with the title GUYUB KOPERASI PENGELOLA SAMPAH, it contains 27 scripts. The digital book publisher is CV Read Me Cipta Media in collaboration with the Faculty of Engineering UNTAR. This PKM activity was attended by 40 participants. It consists of 16 participants are writer practitioners, 13 participants are writer from non-practitioner, and 11 students from the Imaduta team as a  participants for the book launch webinar event.